Unveiling major ethnopharmacological aspects of genus Diospyros in context to its chemical diversity: A comprehensive overview. Issue 12 (22nd September 2022) - Fareed, Nada; El‐Kersh, Dina M.; Youssef, Fadia S.; Labib, Rola M.
Abstract: Diospyros species (DS), "Ebenaceae, " were known for their therapeutic uses in folk medicine since days of yore. Thereafter, scientific evidence related their health benefits to a myriad of chemical classes, for instance, naphthoquinones, flavonoids, tannins, coumarins, norbergenin derivatives, sterols, secoiridoids, sesquiterpenes, diterpenoids, triterpenoids, volatile organic compounds (VOCs), and carotenoids. The available literature showed that more than 200 compounds were isolated and identified via spectroscopic techniques. Many pharmacological activities of DS have been previously described, such as antioxidant, neuroprotective, antibacterial, antiviral, antiprotozoal, antifungal, antiinflammatory, analgesic, antipyretic and cosmeceutical, investigated, and confirmed through versatile in vitro and in vivo assays. Previous studies proved that genus Diospyros is a rich reservoir of valuable bioactive compounds. However, further comparative studies among its different species are recommended for more precise natural source‐based drug discovery and clinical application. Accordingly, this review is to recall the chemical abundance and diversity among different members of genus Diospyros and their ethnopharmacological and pharmacological uses. Practical Applications: Practically, providing sufficient background on both secondary metabolites divergence and pharmacological properties of genus Diospyros has many fruitful aspects. As demonstrated below, extracts and many isolated compounds have significant curative properties, which can lead to the discovery of pharmaceutically relevant alternative substitutes to conventional medicine. Consequently, molecular docking on various receptors can be applied. On the grounds, Naoxinqing tablets, a standardized herbal product containing D. kaki leaves extract, have been patented and recorded in Chinese Pharmacopeia as an approved Traditional Chinese Medicine (TCM) for the treatment of cerebro‐ and cardiovascular diseases, although the underlying mechanism remains under advisement. Moreover, the antimicrobial applications of DS are of considerable concern; since the widespread use of antibiotics resulted in different forms of bacterial resistance, hence, limiting and compromising effective treatment. In addition, as a result of contemporary rampant memory disorders, neuroprotective activities of different extracts of DS became of great emphasis. Abstract :